Antituberculous drugs-induced DRESS syndrome in a patient with type 2 diabetes mellitus - Salas, Antonio (2012)
A case of a 48 year-old male with uncontrolled type 2 diabetes mellitus for the past ten years who presented pulmonary tuberculosis by clinical, radiographic signs and Mycobacterium tuberculosis sputum culture, sensitive to first line treatment drugs, is reported. He received standard treatment with isoniazid, rifampicin, ethambutol, pyrazinamide showing two months later drug hypersensitivity consisting in generalized skin rash, pruritus, positive Coombs anemia, eosinophilia and systemic symptoms compatible with DRESS syndrome (drug rash with eosinophilia and systemic symptoms). The antituberculous drugs were suspended and systemic antihistaminic drugs and corticoids were administered with remission and improvement of symptoms. Afterwards individualized treatment scheme for tuberculosis consisting in minimal hemato-hepatotoxic drugs similar to those indicated to immunosuppressed patients was indicated. Baciloscopies have been negative since.